Key Characteristics of Potential of Development of Regional Economy by Supply Chain Strategy - A.E Demyanenko (International Journal of Supply Chain Management, 2019)
Article is devoted to a research of potential of development of regional economy by employing supply chain management strategy, in aspect of the analysis of productivity of live work in regions and small business, the natural and resource capacity and taxes of regions, key characteristics of potential of development of regional economies. Potential of development of regional economy is considered from positions of a ratio of number of employees of small enterprises and occupied in regional economy, from positions of quantitative characteristics of use of natural and resource potential in regional economies, in a section of export of products of the raw industries (fuel and energy complex, the chemical, forest industry, extraction of metals and metal working). The system of key characteristics of potential of development of regional economies in indicators of the occupied in economy, fixed assets, small business, consumption of energy, innovations, costs of information and communication technologies, specializations of regional economy and financial receipts in the budgetary system of the country is investigated. And also the consumer investment portfolio including consumer spending of the population, region expenses on economy, deposits to financial institutions, balanced results of activity of subjects of managing. The analytical group of regions on the potential of development of regional economies is carried out. The dependence of influence on effectiveness of economic activity not only objectively developed potential of economic development, but also subjective level of its use on the basis of the corresponding regression model according to rated data is revealed.